2005
DOI: 10.1016/j.gene.2004.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of transcription factor DNA binding sites

Abstract: In bioinformatics, binding of transcription regulatory factors to the cognate binding sites is usually described by sequence-specific binding energy, which is estimated from a training sample of sites. This model implies that all binding sites with binding energy above some threshold are functional and site sequence variations should be considered neutral until they do not reduce this energy below the threshold. To quantify this energy, the binding profile (positional weight matrix, PWM) model or consensus-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…However, the relationship between binding, function, and fitness is not well understood (Mirny and Gelfand 2002). In some instances, there exists a correlation between binding energy and substitution rate (Brown and Callan 2004), but this may not always be the case (Kotelnikova et al 2005). Furthermore, nonbinding nucleotides may exert some effect on transcription (Mai et al 2000;Mirny and Gelfand 2002;Abnizova et al 2007;Wozniak and Hughes 2008) and potentially on fitness.…”
mentioning
confidence: 99%
“…However, the relationship between binding, function, and fitness is not well understood (Mirny and Gelfand 2002). In some instances, there exists a correlation between binding energy and substitution rate (Brown and Callan 2004), but this may not always be the case (Kotelnikova et al 2005). Furthermore, nonbinding nucleotides may exert some effect on transcription (Mai et al 2000;Mirny and Gelfand 2002;Abnizova et al 2007;Wozniak and Hughes 2008) and potentially on fitness.…”
mentioning
confidence: 99%
“…This fact clearly indicates that selection does not always favor the maximal strength of an SS, either because the strong SSs are deleterious by themselves (e.g., because excess site strength impedes regulation; Zheng et al 2000; Ast 2004; Garg and Green 2007) or because of other competing selective constraints (Kotelnikova et al 2005; Stergachis et al 2013). Within exonic parts of SSs, such constraints may arise from negative selection on codon usage; in both intronic and exonic parts of SSs, they may also arise due to selection on splicing regulators or some other noncoding function (e.g., Stergachis et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Moses et al (2003) use yeast species for analysis and propose the use of an evolutionary model (Halpern and Bruno 1998) for modelling position-specifi c evolution of TFBSs. Kotelnikova et al (2005) conclude from bacterial binding site data that TFBSs exhibit selectional constraints on degenerate positions also. As would be expected, positions with clear bias towards a single nucleotide tend to maintain their nucleotide preference throughout evolution, implying strong conservation.…”
Section: Abha S Bais* Steffen Grossmann and Martin Vingronmentioning
confidence: 93%
“…Much research has gone into the study of the evolution of binding sites, (McCue et al 2002;Gerland and Hwa 2002;Dermitzakis and Clark 2002;Moses et al 2003;Berg et al 2004;Ludwig et al 2005;Kotelnikova et al 2005;Mustonen and Lässig 2005;Wittkopp 2006). It has been shown that (i) binding sites evolve slower than the surrounding sequences and (ii) they exhibit varying rates of evolution at each position.…”
Section: Abha S Bais* Steffen Grossmann and Martin Vingronmentioning
confidence: 99%